2016
DOI: 10.1111/hae.12986
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of haemophilia A patients after successful immune tolerance induction therapy using a single plasma‐derived FVIII/VWF product: the long‐term ITI study

Abstract: Introduction: Immune tolerance induction (ITI) is a standard intervention to eradicate inhibitors in haemophilic patients. However, information on the long-term condition of patients who eradicated the inhibitor totally or partially after ITI is scarce. Aim: To perform a long-term follow-up to describe the status of patients reported as ITI success in the G-ITI study. Methods: This was an international, multicentre, observational, retrospective study of the 57 haemophilic patients who were reported as ITI succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The FIT group (now 12 years later) concurs with DiMichele et al that historical pre‐ITI peak inhibitor titre and peak inhibitor titre while on ITI are independent predictors of ITI success/failure, but we no longer believe that the inhibitor titre immediately prior to starting ITI on its own is an independent predictor of ITI success/failure given some recent publications and unpublished experiences of FIT group members of starting ITI in patients with HTI without waiting for titres to fall. Other putative prognostic factors, also mentioned for risk stratification by several authors, we regard (much like DiMichele et al did) as being less important …”
Section: Part A: Fit Group Appraisal Of Current Itisupporting
confidence: 58%
“…The FIT group (now 12 years later) concurs with DiMichele et al that historical pre‐ITI peak inhibitor titre and peak inhibitor titre while on ITI are independent predictors of ITI success/failure, but we no longer believe that the inhibitor titre immediately prior to starting ITI on its own is an independent predictor of ITI success/failure given some recent publications and unpublished experiences of FIT group members of starting ITI in patients with HTI without waiting for titres to fall. Other putative prognostic factors, also mentioned for risk stratification by several authors, we regard (much like DiMichele et al did) as being less important …”
Section: Part A: Fit Group Appraisal Of Current Itisupporting
confidence: 58%
“…There is limited information on the effect of prophylaxis on hospitalizations and surgeries (Table ). Jiménez‐Yuste and colleagues conducted a long‐term follow‐up study of 44 patients who had eradicated inhibitors after receiving immune tolerance induction (ITI) therapy . During a median 9 years of follow‐up, there were 79 hospitalizations and 39 surgical/invasive procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Eradication of inhibitors using ITI is the gold standard for patients with HTI in haemophilia A and is the only therapy that can allow the patient to return to a prophylactic FVIII regimen. Studies have shown that long‐term outcomes, including mortality, are greatly improved if inhibitors are eradicated and, furthermore, the long‐term costs associated with inhibitor therapy would likely be reduced by early eradication …”
Section: Discussionmentioning
confidence: 99%